Utilizing OpenStreetMap data to measure and compare pedestrian street lengths in 992 cities around the world - Alexandros Bartzokas-Tsiompras (European Journal of Geography)
Although pedestrian or car-free streets can powerfully produce multiple benefits for urban quality of life, sustainability, and public health very few studies have quantified and analysed their networks in cities all around the world. Given that, in this paper we use OpenStreetMap (OSM) data and integrate the EU and OECD definition of cities to create comparable global indicators concerning the length of pedestrian streets. Our methodology combines OSM data queries and spatial analysis techniques in R. Due to serious inconsistencies observed in other walking-related OSM annotations we use only the pedestrian tag. The results reveal a chasm in car-free development mainly between Southern and Western European cities and their peers in other continents. Since the latter further underlines clear differences in sustainable urban and transport planning cultures around the world, policy analysts and decision-makers can use these findings in order to support data-driven car-free urban planning and thus alleviate the detrimental effects of car traffic on the environment and human health.